The experimental effect of microteaching on the improvement of the teaching skills of selected health professional educators - Alora, Angeles Tan (1983)
Although health professional education aims to produce aims to produce a graduate competent in the field of service and teaching, all health professional educators' curricula are significantly lacking in the learning activities that relate to the development of teaching skills with the exception of the nursing curriculum. Consequently health professional educators generally feel unprepared to effectively communicate their scientific expertise in the classroom situation. Without undergraduate teacher training they are forced to learn to teach ?on the job? or ?by trial and error? Recognizing this deficiency, school administrators throughout the world have set up different types of faculty development programs to develop and increase the teaching efficiency of their faculty members. Seminars and workshops which include how to choose and conduct the more commonly used teaching methods are held. Still, most health professional educators feel there is much to be desired and the search for effective methods of improving teaching efficiency continue. An alternate to present teacher training methods which have been applied by educators of other disciplines is microteaching...